Copper‐Catalyzed Asymmetric Allylic Alkylation of β‐Keto Esters with Allylic Alcohols. Issue 10 (24th February 2017) - Trillo, Paz; Baeza, Alejandro
Abstract: The asymmetric allylic alkylation reaction of β ‐keto esters catalyzed by copper complex t BuBOX‐Cu(OTf)2 employing allylic alcohols as environmentally friendly electrophilic partner, is herein described. This new protocol renders in general the corresponding allylic products with two consecutive all‐carbon stereocenters in good both yields and enantioselectivities and with low to modest diastereoselection. The regioselectivity of the process seems to be governed by the formation of the most stable olefin according to the results obtained when non‐symmetrically substituted alcohols were employed. The scope, limitations and mechanistic aspects of the process are also discussed. Abstract :